Characterization of Mucus-Related Properties of Streptococcus thermophilus: From Adhesion to Induction - Fernandez, Neïké; Wrzosek, Laura; Radziwill-Bienkowska, Joanna M.; Ringot-Destrez, Belinda; Duviau, Marie-Pierre; Noordine, Marie-Louise; Laroute, Valérie; Robert, Véronique; Cherbuy, Claire; Daveran-Mingot, Marie-Line; Cocaign-Bousquet, Muriel; Léonard, Renaud; et al. (Frontiers in Physiology, 2018)
Mucus is a major component of the intestinal barrier involved both in the protection of the host and the fitness of commensals of the gut. Streptococcus thermophilus is consumed world-wide in fermented dairy products and is also recognized as a probiotic, as its consumption is associated with improved lactose digestion. We determined the overall effect of S. thermophilus on the mucus by evaluating its ability to adhere, degrade, modify, or induce the production of mucus and/or mucins. Adhesion was analyzed in vitro using two types of mucins (from pig or human biopsies) and mucus-producing intestinal HT29-MTX cells. The induction of mucus was characterized in two different rodent models, in which S. thermophilus is the unique bacterial species in the digestive tract or transited as a sub-dominant bacterium through a complex microbiota. S. thermophilus LMD-9 and LMG18311 strains did not grow in sugars used to form mucins as the sole carbon source and displayed weak binding to mucus/mucins relative to the highly adhesive TIL448 Lactococcus lactis. The presence of S. thermophilus as the unique bacteria in the digestive tract of gnotobiotic rats led to accumulation of lactate and increased the number of Alcian-Blue positive goblet cells and the amount of the mucus-inducer KLF4 transcription factor. Lactate significantly increased KLF4 protein levels in HT29-MTX cells. Introduction of S. thermophilus via transit as a sub-dominant bacterium (103 CFU/g feces) in a complex endogenous microbiota resulted in a slight increase in lactate levels in the digestive tract, no induction of overall mucus production, and moderate induction of sulfated mucin production. We thus show that although S. thermophilus is a poor mucus-adhesive bacterium, it can promote mucus pathway at least in part by producing lactate in the digestive tract.